2018
DOI: 10.1007/s00253-018-8874-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of shrimp disease incidence via the profiles of gut eukaryotic microbiota

Abstract: One common notion is emerging that gut eukaryotes are commensal or beneficial, rather than detrimental. To date, however, surprisingly few studies have been taken to discern the factors that govern the assembly of gut eukaryotes, despite growing interest in the dysbiosis of gut microbiota-disease relationship. Herein, we firstly explored how the gut eukaryotic microbiotas were assembled over shrimp postlarval to adult stages and a disease progression. The gut eukaryotic communities changed markedly as healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…By contrast, time series data show that the composition of gut microbiota is relatively stable within healthy humans from teenage to old age, though the generality of this pattern is still under debate (Greenhalgh et al, 2016). However, it has been shown that gut eukaryotic microbiota reaches a relatively stable, adult-like status during shrimp adult stage (Xiong et al, 2018b). Alternatively, due to relative short timescale sampling, we have not captured a stable status of gut bacterial community in aquatic animals.…”
Section: Shrimp Ontogeny Governs Its Gut Bacterial Colonizationmentioning
confidence: 84%
See 1 more Smart Citation
“…By contrast, time series data show that the composition of gut microbiota is relatively stable within healthy humans from teenage to old age, though the generality of this pattern is still under debate (Greenhalgh et al, 2016). However, it has been shown that gut eukaryotic microbiota reaches a relatively stable, adult-like status during shrimp adult stage (Xiong et al, 2018b). Alternatively, due to relative short timescale sampling, we have not captured a stable status of gut bacterial community in aquatic animals.…”
Section: Shrimp Ontogeny Governs Its Gut Bacterial Colonizationmentioning
confidence: 84%
“…Alternatively, due to relative short timescale sampling, we have not captured a stable status of gut bacterial community in aquatic animals. However, it has been shown that gut eukaryotic microbiota reaches a relatively stable, adult-like status during shrimp adult stage (Xiong et al, 2018b). Within this context, long-term works are required to test whether an adult-like gut bacterial community is general across biomes.…”
Section: Shrimp Ontogeny Governs Its Gut Bacterial Colonizationmentioning
confidence: 99%
“…Thus, to improve the host's fitness, the colonization of the gut microbiota is filtered from the rearing species pool as a result of deterministic processes. However, when the gut histology and availability niches change as the host ages, the initial "winners" will be reassembled, thereby resulting in a host stage-specific gut microbiota (Greenhalgh et al, 2016;Stephens et al, 2015;Xiong et al, 2018;Yan et al, 2016). Instead, water quality tends to be deteriorative and eutrophic over shrimp cultivation (Xiong et al, 2014;Yang et al, 2018), which stresses shrimp and increases the virulence of pathogens (Penttinen, Kinnula, Lipponen, Bamford, & Sundberg, 2016).…”
Section: Ontogeny and Disease Effects On The Hostbacterial Colonizamentioning
confidence: 99%
“…For this reason, it is mandatory to distinguish the effects of shrimp age from those of disease on the gut microbiota. By distinguishing between age-and disease-discriminatory taxa, a recent study theoretically exemplified that the profiles of gut eukaryotic disease-discriminatory taxa can accurately stratify shrimp health status (20). Similarly, gut bacterial signatures for red-operculum disease are identified at the species level in crucian carp (12).…”
Section: Discussionmentioning
confidence: 99%
“…A few attempts have shown that disease-discriminatory lineages at the species level contribute a higher accuracy than those at the coarse phylum level in diagnosing caries (19) and shrimp disease (20). However, designing specific primers of bacterial 16S rRNA genes at the species level remains challenging.…”
mentioning
confidence: 99%